2010
DOI: 10.1007/s00383-010-2628-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and day of the week variations of perforated appendicitis in US children

Abstract: Perforated appendicitis was more likely to present on Mondays in US children. Although appendicitis is most common in summer months, rates of perforated appendicitis were highest in fall and winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
2
35
1
3
Order By: Relevance
“…Instead, there are reports indicative of a primary infectious event [11], and one study reported on appendicitis appearing in clusters [12]. There are also reports of a seasonal variation of the incidence of acute appendicitis [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Instead, there are reports indicative of a primary infectious event [11], and one study reported on appendicitis appearing in clusters [12]. There are also reports of a seasonal variation of the incidence of acute appendicitis [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Acute Appendicitis (AA) is the most commonly encountered disease in emergency clinics, with about 250,000 cases of appendicitis reported in The United States and 40,000 in England each year (Deng et al, 2010;Simpson et al, 2008). The key form of treatment for the disease is surgery and the mortality, morbidity, and economic cost ratio rise the longer it remains untreated.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmalarda AA yaz ayların-da sık görülmekte iken, bir kısmında da kış aylarında daha sık görülmektedir. [2,13,15,17] Çalışmamızda AA sonbahar ve ilkbahar mevsiminde daha sık görülmekle birlikte istatistiki fark gör-medik. Birçok çalışmada PA kış ve sonbahar aylarında daha sık bildirilmiştir.…”
Section: Discussionunclassified
“…Çocuk-lardaki en sık cerrahi karın ağrısı nedenidir. [1,2] İnsanların %7'si hayatları boyunca apandisit nedeni ile ameliyat edilir. Bununla birlikte doğru tanı %72-94 oranında kalmaktadır.…”
Section: Introductionunclassified